Big Data Security and Privacy Issues: A Review - Nitin Kr. Agrawal (International Journal of Innovative Computer Science & Engineering, 2015)
Big Data has emerged as a necessity in the present world. Most of the human beings are connected to one another through different modes of communications. People share information in different forms. The information that connects people is growing tremendously in large volume which is creating security and privacy concerns. As Big Data technologies are emerging at very fast pace, it is also creating space for security and privacy issues. Until these issues are not addressed properly, it may create obstacles to the fulfillment of expected growth and opportunities and long term success of Big Data. In this paper we review the various domains of Big Data such as healthcare, social media, Internet of things (IOT) and social networking for security and privacy related issues. Keywords: Big Data, security, privacy, healthcare, social media, social networking, IOT